Real Estate Investment and Portfolio Theory - Friedman, Harris C. (Journal of Financial and Quantitative Analysis, 1971)
This paper has shown that the models developed to select common stock port-folios can be adapted to the selection of real estate portfolios and mixed asset portfolios. The concepts are all identical, and as long as return and risk can be quantified, the problems are soluble.The portfolios identified using a small sample indicate that real estate portfolios can have more return and less risk than do common stock portfolios. When the two assets are combined, the real estate assets dominate the resultant portfolios. On an after-tax basis these results are more apparent. The local aspect of real estate versus the national aspect of common stocks is primarily responsible for these results.